2015
DOI: 10.1541/ieejjia.4.654
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Sag Ride-through Performance of Virtual Synchronous Generator

Abstract: The Virtual Synchronous Generator (VSG) is an inverter control structure that supports power system stability by imitating a synchronous machine. Because of the restriction of inverter power and current, the VSG performance under disturbances should be evaluated and enhanced. In this paper, the response of the VSG unit to symmetrical and unsymmetrical voltage sags is assessed. A theoretical analysis that traces the trajectory of the state variable of the system during voltage sags is presented. The analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…the capacitive model (for assessing the SoC) and the voltage model (for terminal voltage calculation of batteries). Considering (11) from [61], it is observed that when BES is applied with VSG, the nominal active power produced by VSG depends on deviations in nominal frequency from the reference value…”
Section: Battery Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…the capacitive model (for assessing the SoC) and the voltage model (for terminal voltage calculation of batteries). Considering (11) from [61], it is observed that when BES is applied with VSG, the nominal active power produced by VSG depends on deviations in nominal frequency from the reference value…”
Section: Battery Energy Storagementioning
confidence: 99%
“…Following VISMA initial design, many other PI controller topologies are used for the VSG controller [9]. The simplicity of the controller design makes it the most common controller adopted for the frequency and voltage controls [10][11][12]. The downside of the controller is the inability to follow the voltage or frequency reference without steady-state error caused by the integral term.…”
Section: Introductionmentioning
confidence: 99%
“…Full state space model is rarely used due to the nonlinearity of the model. Energy functions and Lyapunov method are considered as an efficient technique as in [28,30,35,59], however, it is not feasible for complex systems. If the entire dynamic characteristics of SG is to be reproduced by VSG, the SG model incorporating a full order features of SG has to be modelled [7,22,24] and this would results in 7 th order model.…”
Section: Review Of the Existing Virtual Synchronous Generator Controlmentioning
confidence: 99%
“…When the grid voltage is unbalanced, the proposed control strategy will fail. In [13], a VSG control strategy is proposed, in the case of voltage dips to enhance the VSG's low-voltage ride-through capability so that the inverter would not be off-grid in the event of a voltage dip. In order to ensure that the inverter can work in a complex environment and solve the stability problem of VSG control to further reduce the steady-state error, the ADRC module is added.…”
Section: Introductionmentioning
confidence: 99%